Formulation and evaluation of fexofenadine oral disintegration tablets for improvising patient compliance - Srikanth Choudary Pallothu; Nellutla Sandeepthi (International Journal of Pharmacy and Analytical Research, 2022)
One important drawback of solid dosage forms is the difficulty in swallowing or chewing in some patients particularly pediatric and geriatric patients. Hence, the main aim of this study is to formulate Oral Disintegrating Tablets of Fexofenadine to achieve rapid dissolution, absorption and further improving the bioavailability of the drug. Dissolution test was carried out using USP rotating paddle method (apparatus 2). The stirring rate was 50 rpm. 6.8 pH phosphate buffer was used as dissolution medium (900 ml) and was maintained at 37 ± 10C. Samples of 5ml were withdrawn at pre – determined intervals (2, 4, 6, 8, 10, 15, 20, 25,30 min), filtered and replaced with 5ml of fresh dissolution medium. The collected samples were suitably dilutedwith dissolution fluid, where ever necessary and were analyzed for the Fexofenadine at 412 nm by using UV spectrophotometer. Oral disintegrating Tablets and Films of Fexofenadine were designed with a view to enhance the patient compliance and provide a quick onset of action. Hence it is very conducive to prepare the oral disintegration tablets of fexofinidine.